2020
DOI: 10.1111/joa.13260
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the mammalian neuromuscular junction

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…Taken together with our recently published comparative study of mammalian NMJ morphology, 17 it is clear that considerable heterogeneity of NMJ morphology exists both within and between mammals, including humans. Future studies combining a range of morphological and physiological techniques—such as high-resolution imaging, muscle fibre typing, and electrophysiology—will now be required to ascertain the key determinants of structure–function relationships at the NMJ in both health and disease.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Taken together with our recently published comparative study of mammalian NMJ morphology, 17 it is clear that considerable heterogeneity of NMJ morphology exists both within and between mammals, including humans. Future studies combining a range of morphological and physiological techniques—such as high-resolution imaging, muscle fibre typing, and electrophysiology—will now be required to ascertain the key determinants of structure–function relationships at the NMJ in both health and disease.…”
Section: Discussionmentioning
confidence: 57%
“…TSCs have vital roles to play at the NMJ during development, maturation and after nerve injury or disease. 27 In the current study, we have extended our understanding of species-specific differences at the mammalian NMJ 10 , 17 to show that significant differences are also present in tSC morphology between humans and mice. Despite having similar numbers of tSCs per NMJ, human tSCs were significantly smaller and characterized by a larger non-synaptic area, less AChR coverage, and the presence of both synaptic and non-synaptic placement of nuclei.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The endplate diameter showed changes similar to the endplate area, which are minor values in stretching groups. In Boehm et al 36 work, each animal species has a different value of endplate diameter. Indeed, Estrada-Bonilla et al 37 observed the NMJ morphometric characteristics of the upper limbs of healthy and diabetes mellitusinduced rats.…”
Section: Discussionmentioning
confidence: 99%
“…'fully innervated', 'partially innervated' or 'denervated'), and criteria for NMJ classification can differ, leading to interlaboratory and inter-rater variabilities, thus limiting further analysis [30][31][32][33][34][35][36][37] . Automatic methods include NMJ-morph, an innovative approach based on Image-J software, which has been used to analyse NMJ morphology in different species 38,39 . This platform has widespread use because of its efficiency in measuring morphological NMJ features.…”
Section: Introductionmentioning
confidence: 99%